Non-linear association between the dietary index for gut microbiota and the atherogenic index of plasma: insights from a cross-sectional study - Tian-Ding Liu; Yang-Yang Zheng; Jin-Ying Zhang (Frontiers in Cardiovascular Medicine)
IntroductionThe gut microbiota plays a crucial role in the development of atherosclerosis. The Dietary Index for Gut Microbiota (DI-GM) assesses the impact of diet on gut microbiota, and the Atherogenic Index of Plasma (AIP) serves as a key marker for evaluating atherosclerosis. However, studies exploring the association between DI-GM and AIP remain limited.MethodsData from the 2007–2020 National Health and Nutrition Examination Survey (NHANES) were analyzed, including 15,471 participants. Weighted multivariate linear regression models were employed to evaluate the linear association between DI-GM and AIP, while restricted cubic splines (RCS) were used to assess potential nonlinear relationships.ResultsAfter adjusting for confounding factors, multivariate linear regression analysis demonstrated a significant negative correlation between DI-GM levels and AIP. Each one-point increase in DI-GM was associated with a 0.007-point reduction in AIP (95% CI: −0.012 to −0.002). Categorical analysis further revealed that participants in the DI-GM ≥6 group had significantly lower AIP levels compared to those in lower DI-GM groups (β = −0.038, 95% CI: −0.059 to −0.017; P for trend = 0.007). Restricted cubic spline (RCS) analysis identified a significant non-linear dose-response relationship (P for non-linearity = 0.018) with a threshold at DI-GM = 3.467. Below this threshold, the association was nonsignificant; however, above it, each unit increase in DI-GM corresponded to a 0.011 decrease in AIP (P < 0.001). Subgroup analyses indicated that the relationship between DI-GM and AIP was significantly moderated by age, race/ethnicity, hypertension, and diabetes (P for interaction < 0.05).ConclusionThis study demonstrated a non-linear dose-response relationship between DI-GM levels and AIP, with a significant threshold effect at DI-GM = 3.467. Beyond this threshold, higher DI-GM levels were linked to lower AIP, moderated by age, race/ethnicity, hypertension, and diabetes.